Could Iran fill in the power vacuum in Central Asia? foreign communication theories and analysis of narratives of Leaders - Joevi Roedyati; Yuri Alfrin Aladdin (Publikasi Indonesia, 2024)
Since the beginning of Rusia and Ukraine’s war on February 2022, Central Asian’s military capacitiy was left by the Rusian under the heavy involvement of President Putin in Ukraine. Thus this vacuum, left Iran to eye the opportunities to catch the cooperation with Central Asian countries even more. And also because the political will of Iranian President, Raisi, to engage more and develop more ties with its neighbors and Central Asia countries was detected since the beginning of his term of power August 2021.